Bridging Digital Divide Amidst Educational Change for Socially Inclusive Learning During the COVID-19 Pandemic - Ji Liu (SAGE Publishing, 2021)
During the coronavirus disease-19 (COVID-19) outbreak, many education systems were forced to shut down and move learning and instruction online. The future of learning is here before we know it. While the combination of distance learning and educational technology presents a timely solution combating adverse consequences of school disruptions, there is a real risk of channeling learning opportunities through already-existing forms of digital disparity, especially for marginalized populations. China, as one of the first education systems to experience system-wide school closures due to COVID-19, faces critical challenges of digital divide. To examine pandemic ramifications and effective policy strategies taken to mitigate its unintended consequences, this study leverages an original student learning experience survey collected during the pandemic, and documents national and provincial-level COVID-19 education policy responses in China since the initial outbreak. The study uncovers saliency of access to distance learning and educational technology in shaping student learning experiences, and identifies three compelling policy takeaways from the “Disrupted Classes, Undisrupted Learning” initiative, and discuss emerging lessons drawn for crafting an undivided future for remote distance learning.